2016
DOI: 10.1039/c6cp05523k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the thermoelectric properties of A-site deficient SrTiO3 ceramics by vacancies and carrier concentration

Abstract: Ceramics based on SrLaTiNbO have been prepared by the mixed oxide route. The LaNbO component generates ∼13.4% A-site vacancies; this was fixed for all samples. Powders were sintered under air and reducing conditions at 1450 to 1700 K; products were of high density (>90% theoretical). Processing under reducing conditions led to the formation of a TiNbO second phase, core-shell structures and oxygen deficiency. X-ray diffraction (XRD) confirmed a simple cubic structure with space group Pm3[combining macron]m. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 68 publications
4
63
0
Order By: Relevance
“…Single crystals (SC) are indicated with red dashed lines and polycrystalline samples (PC) are indicated with green solid lines. Literature sources: lanthanum doped STO single crystal (LSTO‐SC), reduced STO single crystal (RSTO‐SC), niobium doped STO single crystal (NSTO‐SC), polycrystalline lanthanum doped STO (LSTO‐PC), polycrystalline lanthanum and niobium doped STO (LNSTO‐PC) …”
Section: Resultsmentioning
confidence: 99%
“…Single crystals (SC) are indicated with red dashed lines and polycrystalline samples (PC) are indicated with green solid lines. Literature sources: lanthanum doped STO single crystal (LSTO‐SC), reduced STO single crystal (RSTO‐SC), niobium doped STO single crystal (NSTO‐SC), polycrystalline lanthanum doped STO (LSTO‐PC), polycrystalline lanthanum and niobium doped STO (LNSTO‐PC) …”
Section: Resultsmentioning
confidence: 99%
“…4,6 We have previously shown that controlled doping on Sr/Ti sites of SrTiO 3 (STO), in addition to controlled vacancy formation within the system, can introduce signicant numbers of charge carriers. 15,16 Cationic vacancies in donor doped STO have been shown to increase carrier concentration and generate oxygen vacancies under reducing environment. These point defects play a crucial role in reducing thermal conductivity by scattering of phonons.…”
Section: Introductionmentioning
confidence: 99%
“…So introducing Sr vacancies demonstrates a valid method for raising the TE performances of SrTiO 3 ‐based materials. In the literature, the contents of Sr vacancies were often related with the substitution contents which resulting in equivalent doping, and most reports were made on single‐doped samples . The physical mechanisms how Sr vacancies influence thermoelectric properties are not very clear until now.…”
Section: Introductionmentioning
confidence: 99%